My Signature Pedagogy, My Tool for Trade - Oli, Indra Kumari (Journal of Janta Multiple Campus, 2025)
It has been more than two decades since I have been teaching English as a subject and experienced the dynamic notions of pedagogy. I have employed mixed approaches to teaching as per the plethora of time, content, and context in my long professional journey. This reflective journaling explores my journey in developing the signature pedagogy of Student Self-Assessment in my ELT class. I share my experience with students' self-assessment tools, strategies, and techniques as a part of my classroom instruction. I followed a qualitative approach and employed an open-ended questionnaire, my observations, students' artifacts, rubrics, criteria, and checklists to collect and analyze the data. I explored that the self-assessment technique developed, creativity, critical thinking, metacognition and autonomy in their English language learning. In this paper, I further discuss my pedagogy's genesis, evolution, implication, and applicability and how it can be transferable beyond English language teaching for sustainable learning.